2017
DOI: 10.3892/mmr.2017.7688
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of serum interleukin-16 in patients with gastric cancer

Abstract: Gastric cancer (GC) is one of the major leading causes of cancer‑associated mortality worldwide. Serum biomarkers have a vital role in diagnosis and prognosis of GC, and interleukin (IL)‑16 may serve as a useful biomarker with prognostic value for human cancers. The current study aimed to evaluate the expression level of serum IL‑16 in patients with GC, and evaluate the diagnostic and prognostic value of IL‑16. ELISA was performed determine the serum IL‑16 levels in patients with GC and healthy controls. Recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Co-expression analysis of TIMER and cBioPortal showed that LRMP was strongly correlated with IL16, KLHL6, EVI2B, SASH3, ARHGAP25, and IKZF1, which are involved in tumorigenesis or immune/inflammatory response (Yang et al, 2017;Choi et al, 2019;Xu et al, 2019;Wang et al, 2020;Mougiakakos et al, 2021;Yang et al, 2021). Our results also showed that LRMP-related gene expression was reduced in LUAD, which was associated with a worse prognosis in patients with LUAD.…”
Section: Discussionsupporting
confidence: 60%
“…Co-expression analysis of TIMER and cBioPortal showed that LRMP was strongly correlated with IL16, KLHL6, EVI2B, SASH3, ARHGAP25, and IKZF1, which are involved in tumorigenesis or immune/inflammatory response (Yang et al, 2017;Choi et al, 2019;Xu et al, 2019;Wang et al, 2020;Mougiakakos et al, 2021;Yang et al, 2021). Our results also showed that LRMP-related gene expression was reduced in LUAD, which was associated with a worse prognosis in patients with LUAD.…”
Section: Discussionsupporting
confidence: 60%
“…Based on previous studies of RANTES, Il-1Ra, IL-6, and IL-8, 11,12,25-27 we chose to evaluate the diagnostic efficacy of SDF-1, IL-16, IL-18, CRELD2, E-selectin, and lipocalin-2. IL-16 is synthesized by several cells, including T cells, eosinophils, dendritic cells, fibroblasts, epithelial cells, and neuronal cells, 28,29 and exhibits diagnostic and prognostic values for patients with diseases, such as gastric cancer, 30 acute myocardial infarction, 31 allergic conjunctival disorders, 32 preeclampsia, 33 Sezary syndrome, 34 and RA. 35 In the present study, we confirmed that elevated SF IL-16 levels represent a biomarker for PJI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of immune-related genes, IL-16 is a pro-inflammatory cytokine that has a variety of biological functions, playing role in the development and homeostasis of the immune system [ 7 ], and stimulating the secretion of tumor-associated inflammatory cytokines including TNF-α, IL-1β, IL-6, and IL-15 [ 8 ]. In addition, polymorphisms in IL - 16 were investigated to be risk of various cancers, including gastric cancer, and the diagnostic and prognostic value of serum IL-16 levels for patients with gastric cancer was also reported [ 9 ]. Transforming growth factor beta-1 (TGF-β1), a multifunctional cytokine, combined it’s receptor ( TGFBR1 ) plays biphasic role in carcinogenesis that, in early stages of cancer, it acts as a tumor suppressor by inhibiting cellular proliferation or by promoting cellular differentiation and apoptosis; in later stages of cancer, however, it turns to be a tumor promoter by stimulating angiogenesis and cell motility, suppressing immune response, and increasing progressive invasion and metastasis [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%